Halley’s Comet (Figure 1) orbits the sun about once every 75 years. Its path can be considered to be a very elongated ellipse. Other comets follow similar paths in space. These orbital paths can be studied using systems of equations. These systems, however, are different from the ones we considered in the previous section because the equations are not linear.
In this section, we will consider the intersection of a parabola and a line, a circle and a line, and a circle and an ellipse. The methods for solving systems of nonlinear equations are similar to those for linear equations.
A system of nonlinear equations is a system of two or more equations in two or more variables containing at least one equation that is not linear. Recall that a linear equation can take the form A x + B y + C = 0. A x + B y + C = 0. Any equation that cannot be written in this form in nonlinear. The substitution method we used for linear systems is the same method we will use for nonlinear systems. We solve one equation for one variable and then substitute the result into the second equation to solve for another variable, and so on. There is, however, a variation in the possible outcomes.
There are three possible types of solutions for a system of nonlinear equations involving a parabola and a line.
Figure 2 illustrates possible solution sets for a system of equations involving a parabola and a line.
Given a system of equations containing a line and a parabola, find the solution.
Solve the system of equations.
x − y = −1 y = x 2 + 1 x − y = −1 y = x 2 + 1Solve the first equation for x x and then substitute the resulting expression into the second equation.
x − y = −1 x = y −1 Solve for x . y = x 2 + 1 y = ( y −1 ) 2 + 1 Substitute expression for x . x − y = −1 x = y −1 Solve for x . y = x 2 + 1 y = ( y −1 ) 2 + 1 Substitute expression for x .
Expand the equation and set it equal to zero.
y = ( y −1 ) 2 + 1 = ( y 2 −2 y + 1 ) + 1 = y 2 −2 y + 2 0 = y 2 −3 y + 2 = ( y −2 ) ( y −1 ) y = ( y −1 ) 2 + 1 = ( y 2 −2 y + 1 ) + 1 = y 2 −2 y + 2 0 = y 2 −3 y + 2 = ( y −2 ) ( y −1 )
Solving for y y gives y = 2 y = 2 and y = 1. y = 1. Next, substitute each value for y y into the first equation to solve for x . x . Always substitute the value into the linear equation to check for extraneous solutions.
x − y = −1 x − ( 2 ) = −1 x = 1 x − ( 1 ) = −1 x = 0 x − y = −1 x − ( 2 ) = −1 x = 1 x − ( 1 ) = −1 x = 0
The solutions are ( 1 , 2 ) ( 1 , 2 ) and ( 0 , 1 ) , ( 0 , 1 ) , which can be verified by substituting these ( x , y ) ( x , y ) values into both of the original equations. See Figure 3.
Could we have substituted values for y y into the second equation to solve for x x in Example 1?
Yes, but because x x is squared in the second equation this could give us extraneous solutions for x . x .
y = x 2 + 1 1 = x 2 + 1 x 2 = 0 x = ± 0 = 0 y = x 2 + 1 1 = x 2 + 1 x 2 = 0 x = ± 0 = 0This gives us the same value as in the solution.
y = x 2 + 1 2 = x 2 + 1 x 2 = 1 x = ± 1 = ± 1 y = x 2 + 1 2 = x 2 + 1 x 2 = 1 x = ± 1 = ± 1Notice that −1 −1 is an extraneous solution.
Solve the given system of equations by substitution.
3 x - y = -2 2 x 2 - y = 0 3 x - y = -2 2 x 2 - y = 0Just as with a parabola and a line, there are three possible outcomes when solving a system of equations representing a circle and a line.
Figure 4 illustrates possible solution sets for a system of equations involving a circle and a line.
Given a system of equations containing a line and a circle, find the solution.
Find the intersection of the given circle and the given line by substitution.
x 2 + y 2 = 5 y = 3 x −5 x 2 + y 2 = 5 y = 3 x −5One of the equations has already been solved for y . y . We will substitute y = 3 x −5 y = 3 x −5 into the equation for the circle.
x 2 + ( 3 x −5 ) 2 = 5 x 2 + 9 x 2 −30 x + 25 = 5 10 x 2 −30 x + 20 = 0 x 2 + ( 3 x −5 ) 2 = 5 x 2 + 9 x 2 −30 x + 25 = 5 10 x 2 −30 x + 20 = 0
Now, we factor and solve for x . x .
10 ( x 2 − 3 x + 2 ) = 0 10 ( x − 2 ) ( x − 1 ) = 0 x = 2 x = 1 10 ( x 2 − 3 x + 2 ) = 0 10 ( x − 2 ) ( x − 1 ) = 0 x = 2 x = 1
Substitute the two x-values into the original linear equation to solve for y . y .
y = 3 ( 2 ) −5 = 1 y = 3 ( 1 ) −5 = −2 y = 3 ( 2 ) −5 = 1 y = 3 ( 1 ) −5 = −2The line intersects the circle at ( 2 , 1 ) ( 2 , 1 ) and ( 1 , −2 ) , ( 1 , −2 ) , which can be verified by substituting these ( x , y ) ( x , y ) values into both of the original equations. See Figure 5.
Solve the system of nonlinear equations.
x 2 + y 2 = 10 x - 3 y = -10 x 2 + y 2 = 10 x - 3 y = -10We have seen that substitution is often the preferred method when a system of equations includes a linear equation and a nonlinear equation. However, when both equations in the system have like variables of the second degree, solving them using elimination by addition is often easier than substitution. Generally, elimination is a far simpler method when the system involves only two equations in two variables (a two-by-two system), rather than a three-by-three system, as there are fewer steps. As an example, we will investigate the possible types of solutions when solving a system of equations representing a circle and an ellipse.
Figure 6 illustrates possible solution sets for a system of equations involving a circle and an ellipse .